EFEK KELAMIN TERHADAP PERFOMA LAHIR ANAK BABI INDUK PERANAKAN DUROC (Effect of sex on birth performace of piglets from duroc crossbred sows) - Yohanes Djegho; Petrus Kune; Johny Nada Kihe (Universitas Nusa Cendana, 2021)
This aim of the research was to know the influence of sex on production performances at birth age of piglets of duroc sow crossbreds. The research was carried out in two breeding farms namely the Instalation of Pig Breeding, village of Tarus, Kupang Regency and the Manise Pig Farm, Village of Oetete, Kupang City, East Nusa Tenggara (NTT). There were 20 heads of duroc crossbred sows. The method used a survey and samples were collected purposively. Samples were all pigles that born during research period from all of duroc sow crossbreds. The variables were litter size, body weight, girth size, and body length. Data was differentiated between males and females and analysed using the t test. The results showed that males had the average of litter size, body weight, girth size and body length of 4.94±1.21 head; 1.42±0.55kg; 23.94±2.80cm and 21.91±4.06cm, respectively; while females had the average of liter size, body weight, girth size and body length of 4.60±1.32 head; 1.39±0.38kg; 23.20±2.76cm and 20.93±4.20cm, respectively. Statistical analysis showed that there was no difference (P>0.05) between males and females from observation variables. Performances of piglets from duroc sow crossbreds for male and female characters such as litter size, birth weight, girth size and body length were relatively similar.